Child Rearing Experiences of Foreign Wives Married to Korean Husbands - Hyang-In Cho Chung, RN, PhD (Elsevier, 2010)
This study was conducted to explore the child rearing experience and associated issues of foreign women married to Korean men. Methods: Eleven foreign women married to Korean men were selected by a purposive and snowball sampling method. Data were collected during the period from May to August, 2007 by a semi-structured interview guide. Transcribed interview data were analyzed using Giorgi's step of phenomenological analysis. Results: The findings revealed six major themes and relevant subthemes: (a) having motherhood, (b) struggling with obstacles, (c) getting lost, (d) finding ways, (e) harvesting; and (f) looking into the future. Conclusions: The participants were experiencing multiple acculturative stressors which negatively affected their capacity for rearing children. However, when they had appropriate support, they were able to achieve many successes. Moreover, they were self-directed and making their best efforts to realize their dreams. This study contributed to the limited knowledge on immigrant women's child rearing experiences. It supported the need for comprehensive community programs that meet a variety of needs for this population and the need for public education.